GIVING ASSIMILATION TO PRISONERS IN CLASS II B CORRECTIONAL INSTITUTIONS SINGARAJA VIEWED FROM THE PERSPECTIVE OF CRIMINOLOGY AND HUMAN RIGHTS - I Wayan Landrawan; Ni Ketut Sari Adnyani (Jurnal Komunikasi Hukum, 2023)
This study aims to determine (1) the implementation of assimilation of prisoners in the Class II B Penitentiary Singaraja; (2) the implementation of the development of prisoners in the assimilation stage at the Class II B Penitentiary in Singaraja; and (3) the prospect of implementing assimilation as an effort to develop prisoners in the Class II B Penitentiary Singaraja in terms of criminology and human rights perspectives. This type of research is a field research with a descriptive qualitative approach. Sources of data in this study are primary, secondary and tertiary data. Data collection techniques with interviews, observations and document studies. This study performs data processing through the process of editing, classifying, verifying, analyzing and concluding. The data analysis technique is descriptive qualitative. The results of the study indicate that the repetition of criminal acts committed by assimilation prisoners, so that it can illustrate that the guidance carried out by the Class II B Singaraja Penitentiary has not been effective.